Analisis Potensi Hutan Rakyat dalam Mendukung Kabupaten Kuningan sebagai Kabupaten Konservasi - Nana Rusyana; Kukuh Murtilaksono; Omo Rusdiana (P4W LPPM IPB, 2020)
Potential Analysis of Community Forests in Supporting Kuningan Regency as a Conservation Regency Kuningan Regency, as one of the conservation regencies in Indonesia, has not been able to produce timber on a large scale because its forest area is dominated by conservation and limited production forest. This has caused the production of timber from the forest area in Kuningan Regency not been able to fulfill market demands. As a result, timber from community forests became an alternative to fulfill those demands. Community forest is forest that grows on land that is burdened with ownership rights of minimum 0.25 ha and canopy cover of minimum 50%, and/or having at least 500 stems/ha in the first year. As the demand for community timber increases, in the long term, the community forest management needs good planning to support the conservation regency policy. Therefore, objectives of this research are (1) to identify the types of community forest timber based on farmers' preferences and the financial feasibility, (2) to analyze land suitability and availability, (3) to analyze the leading commodity, and (4) to suggest the direction of the development regions. Methods of this research are AHP and TOPSIS, financial feasibility calculation (IRR, BC Ratio, NPV), land suitability analysis with matching criteria as well as GIS analysis, LQ, and SSA, together with descriptive analysis. Results showed that the leading types of timber were sengon, mahogany, africa, and teak. All were feasible to be cultivated with the recommended pattern, which was agroforestry. There are 12 districts with community forests as their leading sector, namely Ciawigebang, Cigandamekar, Cimahi, Cipicung, Ciwaru, Darma, Garawangi, Japara, Kramatmulya, Lebakwangi, Luragung, and Nusaherang district. The suggestion for direction of the development regions by type is for the north and east regions to be prioritized for sengon, teak, and africa, while the west and south regions to be prioritized for mahogany.